Treatment of bacterial conjunctivitis in children - T. N. Vorontsova; L. P. Prozornaya (Oftalʹmologiâ)
Conjunctivitis is one of the main forms of ocular infections and occurs from 40.4 to 70.3 % of the total number of patients with inflammatory eye diseases. The purpose of this study was to assess the treatment effectiveness of chronic conjunctivitis various fluorochinolones. Results: There were examined 36 children (72 eyes) with chronic blepharocon-junctivitis. The disease duration was 3 months or more. To clarify the etiology blepharoconjunctivitis all patients was taken from the conjunctival cavity material for planting on the microflora. The sensitivity of microflora to antibiotics used in the form of eye dosage forms, determined by discodiffution method. In addition, bacterial conjunctivitis character was confirmed by cytology material scrapings from the conjunctiva. In children with chronic blepharoconjunctivitis content in crops conjunctival cavity often detected Staphylococcus aureus (61,2 %, n = 22). In 11 cases determined by mixed infection (30.65 %), then there is an association with Staphylococcus aureus or Staphylococcus epidermidis with streptococcus. In 2 children has been detected Staphylococcus epidermidis (5,5 %). Sowing proved sterile only one child (2.7 %). All patients were divided into 3 groups. In each group of children received instillation one from fluoroquinolones, which was marked by the minimum resistance of Staphylococcus aureus. The first group consisted of 14 children (28 eyes) who were buried ofloxacin 0.3 %, the second — 10 patients (20 eyes) treated with 0.3 % ciprofloxacin, and a third — 12 patients (24 eyes) who received the drug instillation Signitsef (SENTISS). Conclusion: the treatment of chronic bacterial conjunctivitis instill drops containing a solution of antibacterial drugs of the fluoroquinolones, has high clinical efficacy. The dynamics of the main clinical signs of chronic blepharoconjunctivitis was more pronounced on the background of 0.5 % levofloxacin (Signitsef, SENTISS).